Refraksi Yuridis Penetapan Program Legislasi Nasional di DPR RI - Mira Fajriyah (Jurnal Konstitusi, 2016)
Prolegnas is a law developmental transformation after the amendment of UUD NRI 1945. However, the effectuation of Prolegnas’s decree by DPR RI always shows the less of law reformation level, either on qualitative measure or the quantitative. This research has a focus to arrange a law prescription of juridical refraction on  the effectuation of Prolegnas’s decree by DPR RI. The research explains the peak of trouble of the effectuation of Prolegnas’s decree, consists of low level of consistency and realization, the incompatibility between Prolegnas’s substances and mandated by legislation and the list of draft bill which not based on an academic research. Those are a logical clause of two juridical refraction stages, viz, formal concession and substance concession (prospective  orientation).